(untitled) (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Chronic recurrent mutlifocal osteomyelitis (CRMO) is an extremely rare skeletal disorder in the younger population. It presents with multifocal bony lesions that often mimic more sinister diagnoses such as neoplasm. The cause of this condition remains unknown and there is limited evidence on effective treatment. Presentation of Case: A 9-year-old girl presented to our institution with non-traumatic onset of left leg pain. After failed conservative management, radiographs and MRI were obtained exhibiting a bony lesion of the proximal tibia resembling osteomyelitis. The patient was non-responsive to antibiotics, so corticotomy and drainage was done in which only blood came out of the lesion, no pus was seen. Patient improved dramatically but again she developed similar symptoms and signs on right leg. Biopsy from left leg suggested no significant findings. Discussion: Chronic recurrent multifocal osteomyelitis presents in patients with periodic fevers, bone pain and bone lesions that can develop anywhere in the body. This is a rare disease, which has been found to affect more girls than boys. Conclusion: CRMO should be considered as a differential diagnosis for chronic bone pain with affinity for the long bones of the lower extremity in children and adolescents. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(2): 51-55